"Some Sanity and Love": The Cold War, Antarctic Treaty, and Fids' identity, 1957–1958. (8th November 2019) - Avery, Andrew J.
Abstract: In 1942, the British government created the Falkland Islands Dependencies Survey (FIDS) to enforce sovereignty over the Antarctic Peninsula. The small groups of men who worked for the Survey called themselves Fids. During the late 1950s when Antarctic sovereignty was being hotly debated and worked out by national governments, Fids serving at British bases criticised the British government's use of science as a bargaining chip. Using in-house magazines written and printed at FIDS bases and oral histories, this article examines how Fids viewed Antarctic politics and how those events influenced daily life at bases on the Peninsula.